Suvremena tehnologija prijevoza i njen utjecaj na organiziranje i cijenu prijevoza - Smrček, Antun (Promet - Traffic&Transportation, 2012)
Transportation costs depend upon the conditions in which the service is operated. It is necessary to introduce new organization of the transportation process. New organization has to make it possible for individual vehicles of the motor pool to spend as much time as possible transporting freight. New technological developments in tntcks manufacturing create the possibilities for reducing the freight loading/ unloading process to a single minute or less. This further enables better making use of the driver’s working time. Also, vehicles could be changed in transport of special loads. This then increases the efficiency of the motor pool and decreases the transportations costs.